Biosynthesis, structure and antioxidant activities of xanthan gum from Xanthomonas campestris with additional furfural. (15th July 2019) - Kang, Yan; Li, Panyu; Zeng, Xiaotong; Chen, Xi; Xie, Yi; Zeng, Yu; Zhang, Yongkui; Xie, Tonghui
Graphical abstract: Highlights: The effect of additional furfural on xanthan gum production was explored. Low concentration of furfural promoted cell growth and kept steady xanthan yield. Furfural altered acetyl, pyruvate and glucuronic acid contents of xanthan products. 1 g·L –1 of furfural provided product a desirable hydroxyl radical scavenging effect. Abstract: Lignocellulosic-like materials are potentially low-cost fermentation substrates, but their pretreatment brings about by-products. This work investigated the effects of furfural on xanthan gum (XG) production, and product quality was evaluated by structure, viscosity and antioxidant capacities. Xanthomonas campestris maintained steady polysaccharide yield (above 13 g·L –1 ) with enhanced cell growth at low furfural concentrations (below 3.2 g·L –1 ). The products were verified as XG by FT-IR, XRD, NMR and monosaccharide analysis. Moreover, they were found to have reduced acetyl, rising pyruvate and up-to-down glucuronic acid groups as increasing furfural concentration. Furthermore, XG product with 1 g·L –1 furfural addition showed the best hydroxyl scavenging effects, though reducing powers presented no variation. It was demonstrated that furfural, the common hydrolysis by-product, was not necessarily an inhibitor for fermentation, and an appropriate amount of furfural was beneficial to XG production with steady yield and good quality.